Sports related injuries of the meniscus (Clinics in Sports Medicine, 2012)
The evaluation and management of meniscus tears continues to be an evolving and dynamic segment of the sports medicine world. The goal of this issue of Clinics in Sports Medicine is to keep the interested practitioner up to date on the latest procedures and technologies involving the repair of meniscus tears.